2023
DOI: 10.1182/bloodadvances.2022008392
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bending and sphingomyelinase-associated, sulfatide-dependent hypoxic adhesion of sickle mature erythrocytes

Abstract: Abnormal erythrocyte adhesion due to polymerization of sickle hemoglobin is central to the pathophysiology of sickle cell disease (SCD). Mature erythrocytes constitute >80% of all erythrocytes in SCD, and the relative contributions made by erythrocytes to acute and chronic vasculopathy in SCD are not well understood. Here, we show that the bending stress exerted on the erythrocyte plasma membrane by the sickle hemoglobin polymerization under hypoxia enhances sulfatide-mediated abnormal mature erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For instance, our recent published study shows that sickle reticulocytes and sickle mature RBCs bear different adhesion characteristics under hypoxia, which is membrane-sulfatide dependent and varies from patient to patient. 94 Third, manual counting of RBC adhesive and occlusive events in the microchannel greatly hinders the OcclusionChip potential for clinical translation. Future work will prospectively focus on demonstrating the clinical utility of the functionalized OcclusionChip assay as an in vitro therapeutic benchmark in a larger patient population with homozygous SCD, under normoxic and hypoxic conditions, and monitoring diverse treatments including conventional, targeted, or curative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our recent published study shows that sickle reticulocytes and sickle mature RBCs bear different adhesion characteristics under hypoxia, which is membrane-sulfatide dependent and varies from patient to patient. 94 Third, manual counting of RBC adhesive and occlusive events in the microchannel greatly hinders the OcclusionChip potential for clinical translation. Future work will prospectively focus on demonstrating the clinical utility of the functionalized OcclusionChip assay as an in vitro therapeutic benchmark in a larger patient population with homozygous SCD, under normoxic and hypoxic conditions, and monitoring diverse treatments including conventional, targeted, or curative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…HbSS whole blood was diluted 1:4 with PBS for the dilution experiment. Hypoxic conditions (SpO2 of approximately 83% in the blood sample), using a micro-tube gas exchanger as we described previously 23 . To prevent non-specific cellular interactions, microchannels were incubated with bovine serum albumin at 4°C overnight, and additionally, 250 μ l of bovine serum albumin was injected into the microchannels at room temperature with a 5 μ l/min flow rate 2 hours prior to the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…MBM also has the potential of revealing more subtle dynamical relationships that have not been systematically explored, for example how morphological features of cells are correlated with dynamical behaviors at the single-cell level. For example, a longstanding question about sickle red blood cells is whether elongated, irreversibly sickled cells are more adhesive to endothelium than sickle discocytes 23 . In Fig 8 a, we show MBM data for the relationship between average sickle red blood cell eccentricity (calculated over the entire cell trajectory) and adhesion duration to laminin, revealing a significant negative trend ( p < 0.03, linear regression): cells with longer adhesion durations are slightly less elongated on average.…”
Section: Mainmentioning
confidence: 99%

Motion Blur Microscopy

Goreke,
Gonzales,
Shipley
et al. 2023
Preprint
Self Cite
“… 53 , 81 , 82 A recent finding indicated that the polymerization of HbS added bending stress on the erythrocyte membrane. 83 Upregulated sphingomyelinase caused erythrocytes to produce higher-than-normal levels of sulfatides, promoting abnormally adherent. Meanwhile, the increase in plasma Hb and free heme during hypoxia activates the vascular endothelium, causing sickle erythrocyte adhesion 84 and increased adhesion to laminin.…”
Section: Hypoxia Affects Erythrocyte Membrane Propertiesmentioning
confidence: 99%